Game theory and strategy in medical training. Issue 11 (November 2016) - Blake, Amy; Carroll, Bryan T
Abstract : Objective: This paper analyses how game theory can provide a framework for understanding the strategic decision‐making that occurs in everyday scenarios in medical training and practice, and ultimately serves as a tool for improving the work environment and patient care. Game theory has been applied to a variety of fields outside of its native economics, but has not been thoroughly studied in the context of health care provision. Methods: The paper discusses four of the most common 'games' and applies each to a scenario in medicine to provide new insight on the incentives and drivers for certain types of behaviour and a deeper understanding of why certain results are valued more strongly than others. Conclusions: Using game theory as an integrative tool, in conjunction with good judgement and a sound knowledge base, trainees and physicians can work to better recognise where competing priorities exist, understand the motivations and interactions of the various players, and learn to adjust their approaches in order to 'change the game' when their preferred outcome is not the most likely one. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.